2017
DOI: 10.1128/jcm.01087-17
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium Macrolide and Fluoroquinolone Resistance Detection and Clinical Implications in a Selected Cohort in New Zealand

Abstract: has been associated with infections of the genitourinary tract, and prevalence is secondary to The clinical observation of increasing treatment failure indicating antibiotic resistance, especially in cases of recurrent urethritis, has been confirmed by molecular testing. Mutations in the 23S rRNA gene can cause macrolide resistance, and topoisomerase/gyrase mutations can cause fluoroquinolone resistance. In this study, 115 DNA-positive samples were analyzed. Eighty-nine (77.4%) samples had a 23S rRNA mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 23 publications
(27 reference statements)
2
17
5
Order By: Relevance
“…The amino acid changes at G81, S83 and D87, have been previously reported as being associated with uoroquinolone resistance in M. genitalium and other closely related organisms [44,46,49]. Although the majority of published reports have shown the parC S83N and S83I substitution as the two most prevalent base changes at position 248, we nd that the S83I substitution accounted for 71.8% (79/110), signi cantly higher reports from Japan (13.0-23.2%) [42], New Zealand (16.7%) [48], and southwestern France (9.1%) [66]. Among the 139 samples successfully ampli ed DNA sequences of parC gene, we observed an exorbitantly high mutation rate of 77.7%.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The amino acid changes at G81, S83 and D87, have been previously reported as being associated with uoroquinolone resistance in M. genitalium and other closely related organisms [44,46,49]. Although the majority of published reports have shown the parC S83N and S83I substitution as the two most prevalent base changes at position 248, we nd that the S83I substitution accounted for 71.8% (79/110), signi cantly higher reports from Japan (13.0-23.2%) [42], New Zealand (16.7%) [48], and southwestern France (9.1%) [66]. Among the 139 samples successfully ampli ed DNA sequences of parC gene, we observed an exorbitantly high mutation rate of 77.7%.…”
Section: Discussioncontrasting
confidence: 53%
“…AMR studies of uoroquinolone resistance in M. genitalium DNA tend to amplify the quinolone-resistance determining region (QRDR) of the gyrA gene and the corresponding region of the parC gene from M. genitalium DNA [47]. Antibiotic resistance of M. genitalium to both macrolides and quinolones have been found in Japan, Australia, and New Zealand since 2008 [33,38,44,48,49]. This disturbing trend suggests that the AMR dilemma attributable to M. genitalium is spreading and becoming even more virulent [33,44,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of published reports have shown the ParC S83N and S83I alteration as the two most prevalent base change at position 248, our study revealed that the S83I alteration were predominating accounting for 71.8% (79/110), significantly higher than those from Japan (13.0-23.2%) [68], New Zealand (16.7%) [56], and southwestern France (9.1%) [74]. Japan [88], this trend is rarely found in extant prior studies.…”
Section: Summary Of Amr Clinical Studies In Chinacontrasting
confidence: 76%
“…Fluoroquinolone resistance is attributed to alternations the GyrA subunit in DNA gyrase (which is composed of two gyrA and two gyrB subunits), or the ParC subunit of topoisomerase IV (which is composed of two parC and two parE subunits) [ Multidrug resistance is present in both macrolide and fluoroquinolone resistance-associated mutations in M. genitalium being reported in Japan, Australia and New Zealand since 2008 [41,52,56,57]. This disturbing trend suggesting that the AMR dilemma attributable to M. genitalium is spreading and becoming even more virulent [41,52,56,57].…”
Section: Amr Problems Related To M Genitalium Treatment Interventionsmentioning
confidence: 99%
“…High MRMM frequency in M. genitalium has been described before ( 25 36 ) and is thought to be a consequence of using the single-dose azithromycin treatment regimen for C. trachomatis infections without excluding the presence of M. genitalium nongonococcal urethritis in men, M. genitalium infections, or both ( 18 , 19 ). To our knowledge, the decreasing number of MRMMs observed in M. genitalium from our study population in 2017 compared with 2016 has not been described before; however, compared with 2014 and 2015, the MRMM prevalence trend is increasing.…”
Section: Discussionmentioning
confidence: 92%